2021
DOI: 10.1038/s41598-021-01782-6
|View full text |Cite|
|
Sign up to set email alerts
|

Biphasic (5–2%) oxygen concentration strategy significantly improves the usable blastocyst and cumulative live birth rates in in vitro fertilization

Abstract: Oxygen (O2) concentration is approximately 5% in the fallopian tube and 2% in the uterus in humans. A “back to nature” approach could increase in vitro fertilization (IVF) outcomes. This hypothesis was tested in this monocentric observational retrospective study that included 120 couples who underwent two IVF cycles between 2014 and 2019. Embryos were cultured at 5% from day 0 (D0) to D5/6 (monophasic O2 concentration strategy) in the first IVF cycle, and at 5% O2 from D0 to D3 and 2% O2 from D3 to D5/6 (bipha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In hypoxic environments, O 2 tension promotes the development of mouse blastocysts and reduces apoptosis by regulating HIF-2α, thereby increasing the expression of antioxidant enzymes, such as MnSOD, PRDX5, and vascular endothelial growth factor (VEGF) 44 . In bovine and mouse preimplantation embryos, biphasic O 2 (7-2% or 5-2%) changes the expression of genes involved in embryonic metabolism 9,45,46 47 . Generally, biphasic O 2 (5-2%) cultures are associated with considerably increased cumulative live birth and total blastocyst and usable blastocyst formation rates 47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In hypoxic environments, O 2 tension promotes the development of mouse blastocysts and reduces apoptosis by regulating HIF-2α, thereby increasing the expression of antioxidant enzymes, such as MnSOD, PRDX5, and vascular endothelial growth factor (VEGF) 44 . In bovine and mouse preimplantation embryos, biphasic O 2 (7-2% or 5-2%) changes the expression of genes involved in embryonic metabolism 9,45,46 47 . Generally, biphasic O 2 (5-2%) cultures are associated with considerably increased cumulative live birth and total blastocyst and usable blastocyst formation rates 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In bovine and mouse preimplantation embryos, biphasic O 2 (7-2% or 5-2%) changes the expression of genes involved in embryonic metabolism 9,45,46 47 . Generally, biphasic O 2 (5-2%) cultures are associated with considerably increased cumulative live birth and total blastocyst and usable blastocyst formation rates 47 . Under biphasic O 2 conditions, changing the relative abundance of anabolic amino acids and metabolites involved in redox homeostasis and the differential expression level of MUC1 in TE cells may improve the development of human embryos 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture under 2% O 2 tension led to a higher blastulation rate (40.2 versus 22.5%) and a higher utilization rate (36.8 versus 21.3%) [ 10 ]. A recent study showed that the total and usable blastocyst rates (44.4 versus 54.8% and 21.8 versus 32.8%, respectively) were significantly higher under 2% O 2 tension from day 3 onwards [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional IVF (cIVF) or intra cytoplasmic sperm injection (ICSI) technique were used as appropriate. IVF procedure was performed in our unit as previously described ( 22 ). At D3, embryo morphology was graded using a standard system including number, size and uniformity of blastomeres, degree of fragmentation and the presence of multinucleated blastomeres.…”
Section: Methodsmentioning
confidence: 99%